Synthesis of α-(perfluoroalkylsulfonyl)propiophenones: a new set of reagents for the light-mediated perfluoroalkylation of aromatics - Castillo-Pazos, Durbis J.; Lasso, Juan D.; Li, Chao-Jun (Beilstein Journal of Organic Chemistry, 2022)
In response to the demand for late-stage perfluoroalkylation in synthetic chemistry, we report the synthesis of a series of bench-stable α-(perfluoroalkylsulfonyl)propiophenones. Their application as photocleavable reagents was tested with electron-rich aromatics under metal-free, redox- and pH-neutral conditions to enable late-stage perfluorooctylation, perfluorohexylation, and perfluorobutylation.
Keywords: α-(perfluoroalkylsulfonyl)propiophenones; innate functionalization; late-stage functionalization; light-mediated perfluoroalkylation; perfluoroalkyl sulfinates

(untitled) - Glüge, J.; Scheringer, M.; Cousins, I. T.; DeWitt, J. C.; Goldenman, G.; Herzke, D.; Lohmann, R.; Ng, C. A.; Trier, X.; Wang, Z. (Environ. Sci.: Processes Impacts, 2020)

(untitled) - Tiers, G. V. D. (J. Am. Chem. Soc., 1960)

(untitled) - McLoughlin, V. C. R.; Thrower, J. (Tetrahedron, 1969)

(untitled) - Castillo-Pazos, D. J.; Lasso, J. D.; Li, C.-J. (Org. Biomol. Chem., 2021)

(untitled) - Barata-Vallejo, S.; Bonesi, S. M.; Postigo, A. (RSC Adv., 2015)

(untitled) - Postigo, A. (Eur. J. Org. Chem., 2018)

(untitled) - Barata-Vallejo, S.; Cooke, M. V.; Postigo, A. (ACS Catal., 2018)

(untitled) - Yerien, D. E.; Lantaño, B.; Barata‐Vallejo, S.; Postigo, A. (ChemCatChem, 2021)

(untitled) - Liu, P.; Liu, W.; Li, C.-J. (J. Am. Chem. Soc., 2017)

(untitled) - Zimmerman, H. E.; Hancock, K. G.; Licke, G. C. (J. Am. Chem. Soc., 1968)

(untitled) - Sheehan, J. C.; Wilson, R. M.; Oxford, A. W. (J. Am. Chem. Soc., 1971)

(untitled) - Sheehan, J. C.; Wilson, R. M. (J. Am. Chem. Soc., 1964)

IOP Conference Series: Earth and Environmental Science, Volume 100 - Song, H. (Research progress on trifluoromethyl-based radical reaction process, 1st International Global on Renewable Energy and Development (IGRED 2017), Singapore, 22.12.2017-25.12.2017, 2017)

(untitled) - Fujiwara, Y.; Dixon, J. A.; O’Hara, F.; Funder, E. D.; Dixon, D. D.; Rodriguez, R. A.; Baxter, R. D.; Herlé, B.; Sach, N.; Collins, M. R.; Ishihara, Y.; Baran, P. S. (Nature, 2012)

(untitled) - O’Hara, F.; Blackmond, D. G.; Baran, P. S. (J. Am. Chem. Soc., 2013)

New Horizons of Process Chemistry: Scalable Reactions and Technologies - Fujiwara, Y.; Baran, P. S. (Radical-Based Late Stage C–H Functionalization of Heteroaromatics in Drug Discovery, 2017)

(untitled) - Aziz, J.; Hamze, A. (Org. Biomol. Chem., 2020)

(untitled) - Liang, S.; Hofman, K.; Friedrich, M.; Manolikakes, G. (Eur. J. Org. Chem., 2020)

(untitled) - Huang, X.-T.; Long, Z.-Y.; Chen, Q.-Y. (J. Fluorine Chem., 2001)

(untitled) - Huang, W.; Huang, B.; Wang, W. (Acta Chim. Sin. (Chin. Ed.), 1985)

(untitled) - Cao, H.-P.; Chen, Q.-Y. (J. Fluorine Chem., 2007)

(untitled) - Dmowski, W.; Piasecka-Maciejewska, K. (J. Fluorine Chem., 2005)

(untitled) - Finkelstein, H. (Ber. Dtsch. Chem. Ges., 1910)

(untitled) - Li, L.; Liu, W.; Zeng, H.; Mu, X.; Cosa, G.; Mi, Z.; Li, C.-J. (J. Am. Chem. Soc., 2015)

(untitled) - Beatty, J. W.; Douglas, J. J.; Cole, K. P.; Stephenson, C. R. J. (Nat. Commun., 2015)

(untitled) - Yin, D.; Su, D.; Jin, J. (Cell Rep. Phys. Sci., 2020)

(untitled) - Lasso, J. D.; Castillo-Pazos, D. J.; Li, C.-J. (Chem. Soc. Rev., 2021)